Para aprender com a Terra: memórias e notícias de Geociências no espaço lusófono - M. H. Henriques (Documentos, 2012)
This work brings together a series of contributions presented at the 1st International Conference in Geosciences in the Community of Portuguese-Speaking Countries (CPLP), which took place on 14th to 16th May 2012 in the Auditorium of the Rector's Office of the University of Coimbra. It presents works produced by various teams affiliated to different institutions of the CPLP, offering innovative educational approaches, aiming at school contexts and at scenarios outside the classroom. It uses not only conventional methods, such as school textbooks, but also fictionalized narratives, without overlooking the educational potential of many of the places located in Lusophone countries, with their enormous heritage value.